The Effects of Gonadotropin Releasing Hormone Analogue Therapy on Girls with Gonadotropin-dependent Precocious Puberty - Yi-Ching Tung; Jing-Sheng Lee; Wen-Yu Tsai; Pei-Hung Hsiao (Journal of the Formosan Medical Association, 2007)
It has been reported that gonadotropin releasing hormone analogue (GnRHa) therapy can improve the adult height of patients with gonadotropin-dependent precocious puberty. The purpose of this study was to evaluate the effect of GnRHa on the adult height of girls with gonadotropin-dependent precocious puberty and the adverse effects of such therapy. Methods: Between 1989 and 2006, 11 girls with gonadotropin-dependent precocious puberty who had been treated with GnRHa and reached their adult height were enrolled in the present study. Follow-up studies of bone age, pelvic sonography and GnRH test were done regularly during the period of treatment. All patients had bone mineral density examined at least 2 years after completion of GnRHa therapy. Results: GnRHa therapy was initiated at the age of 8.0 ± 1.5 years. The predicted adult height immediately before GnRHa therapy was 146.7 ± 4.8 cm (−2.3 ± 0.9 standard deviation [SD]). The duration of GnRHa therapy was 4.7 ± 1.8 years. The adult height of the patients was 156.3 ± 4.3 cm (−0.6 ± 0.8 SD), which is similar to their target height of 157.0 ± 4.5 cm (−0.5 ± 0.8 SD). The uterine sizes and gonadotropin responses to GnRH stimulation were well suppressed during treatment. Menstruation resumed 9.2 ± 5.9 months after the discontinuation of treatment in these patients. Forty-five percent of patients had lumbar bone mineral density less than 1 SD below that of normal young Taiwanese adults in the Taipei region. Conclusion: GnRHa therapy can improve the adult height of patients with gonadotropin-dependent precocious puberty. However, 45% of patients had decreased bone accretion during therapy.